Experimental Study on Frosting Characteristics of Three-row Finned Tube Heat Exchanger with Different Fin Pitch - Xiao Hongxin; Chen Guansheng; Liu Liangde; Luo Chaohong; Liu Xiangyun; Li Jianguo (Zhileng xuebao)
The limitations of non-uniform frosting along the direction of air flow and large frost mass in the first row of the finned tube heat exchanger of an air-source heat pump under low ambient temperature may cause a short defrost interval, heating capacity decline, and other negative effects. To overcome these challenges, an experimental study was conducted on finned tube heat exchangers with different fin pitches operating at low ambient temperatures. The results show that finned tube heat exchangers with different fin pitches can prolong the frosting blocking time of the windward tube row. This inhibits the frosting rate and frost quality and reduces the heat loss caused by frequent defrosting, which is also beneficial for increasing the total heat transfer in one defrosting cycle. The heat transfer capacity of the finned coil heat exchanger with variable pitch is higher in the middle and later stages of frosting. Under a reasonable combination of the fin pitch, the finned coil heat exchanger with variable pitch can prolong the frosting blocking time of the windward side of the heat exchanger without losing substantial heat transfer capacity.